An Enhanced Cryptographic Scheme Utilizing Byte Rotation and LU Decomposition - Joseph, Roma Smart; Kaushal, Chaitanya (Journal of Research in Science and Engineering, 2026)
This study introduces a novel cryptographic scheme integrating Byte Rotation and LU decomposition to enhance encryption security. The encryption process employs Byte Rotation alongside a lower triangular matrix as the encryption key, while decryption is achieved using inverse Byte Rotation with an upper triangular matrix. The proposed method strengthens data security by increasing confusion and diffusion, making cryptanalysis more challenging. The results suggest that this dual - layer encryption framework provides a robust and computationally efficient approach to secure communications.